SISTEM PERDAGANGAN SAPI ORANG MADURA DI KECAMATAN TEMBILAHAN KABUPATEN INDRAGIRI HILIR - Abdul Halim; Jonyanis " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
The trade carried out by Madurese is different from the others. They can last until now. The existence of a social interaction and regularity in groups so that they are able to compete with the times. In this qualitative study using Observation, Interview, and Documentation techniques. The purpose of this study is to find out what systems are used by Madurese to be able to compete with others. The social relations that exist between fellow Madurese are felt while they remain in the same employment status. Social relationships that are established from one another will form a one system. The results of this study are to find out how the Madurese trading system and know how strong the social of Madurese in maintaining the tradition of being a cattle trader. The mention of this tradition is also a factor for Madurese who continue to practice what their parents or parents have taught them. They will not easily let go of the activities that have been taught. In addition to maintaining the cultural value of it also maintains the socioeconomic value of the community. Keywords: Trade, Tradition, System, Social Relations